2013
DOI: 10.1007/s11274-013-1286-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community biogeographic patterns in the rhizosphere of two Brazilian semi-arid leguminous trees

Abstract: Arid environments are regular and well distributed over all continents and display drought characteristics whether full-time or seasonal. This study aims to characterize how the microbial communities of the rhizosphere of two leguminous trees from the Brazilian semi-arid biome the Caatinga are geographically and seasonally shaped, as well as the factors driving this variation. With that purpose, the soil rhizosphere from two leguminous trees (Mimosa tenuiflora and Piptadenia stipulacea (Benth.) Ducke) were sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Although there has not been a significant effect of environmental variables over the community structure through CCA, soil variability might have influenced this variation, since some of these characteristics (i.e. temperature, moisture content, nutrient availability) have been pointed out as the main drivers of soil bacterial communities variability (Fierer et al ., ; Pasternak et al ., ) as observed for the diversity in the Caatinga based on gene markers (SSU and amo A gene) (Kavamura et al ., ; Lançoni et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Although there has not been a significant effect of environmental variables over the community structure through CCA, soil variability might have influenced this variation, since some of these characteristics (i.e. temperature, moisture content, nutrient availability) have been pointed out as the main drivers of soil bacterial communities variability (Fierer et al ., ; Pasternak et al ., ) as observed for the diversity in the Caatinga based on gene markers (SSU and amo A gene) (Kavamura et al ., ; Lançoni et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…This study represents one of the first analyses of Brazilian semiarid metagenomes conducted to date with over 250 Mb of metagenomic data obtained from six different libraries. Nevertheless, we could detect some patterns in the datasets that highlight the same trend in the shifts of communities when compared with studies of the same biome (Kavamura et al ., ; Lançoni et al ., ). Furthermore, microbial communities found in semiarid soils are known to display two different life moments, one of high activity (Barnard et al ., ) and increased diversity characterized by the presence of Proteobacteria due to the presence of rain, and another one of lower activity and abundance of Actinobacteria, in a strategy of preparedness.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies investigating the microbial communities associated with diverse plant hosts have demonstrated that sample type (plant compartment), host species, geographic location, and season are all capable of influencing community composition, although the extent to which each plays a role has varied from study to study (DeAngelis et al, 2008;Lundberg et al, 2012;Lanc ßoni et al, 2013;Peiffer et al, 2013;Mendes et al, 2014;Edwards et al, 2015;Zarraonaindia et al, 2015). Most previous studies have focused on prokaryotic communities, providing limited insights into the forces shaping plant-associated fungal communities.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was not possible to detect any significant difference in the archaeal community for the two plants, neither in relation to the different points nor in relation to seasons [116]. …”
Section: Archaea In Soilsmentioning
confidence: 99%